Electron transfer to decorated graphene oxide particles - Miao, R; Chen, L; Shao, L; Zhang, B; Compton, R (Wiley, 2019)
Graphene oxides (GOs) are popular catalyst supports for precious metals in nanoparticle form. The hydrogen oxidation reaction (HOR) and the hydrogen evolution reaction (HER) on individual GO platelets decorated with Pd nanoparticles (Pd/GOs) were investigated and suggest that the catalytic activity is confined to zone physically close to the point of electrical contact between platelet and electrode with just a fraction of the platelet active.